Incontri arturiani. La famiglia di 'acoint' da Chrétien de Troyes alla «Mort Artu» (Carte Romanze, 2020)
The lexical family of acoint is amply attested in Old French, and from there it expanded into other Romance as well as into Germanic languages. In medieval narratives, and in particular in both prose and verse Arthurian romances, this lexical family oftens occurs in the representation of the courtly society with its relations and encounters – whether everyday or exceptional. Between Chrétien de Troyes and the Lancelot en prose, it is possible to identify some shared trends: for example, we might find among the uses of the lemmata of this family as theme-words, some instances of their use as key-words. Nevertheless, there is a difference in verse texts compared to those in prose. The former marks key-words mainly through rhetorical-stylistic devices while the  the latter achieves this goal mainly through narrative mechanisms, from the use of episodes which mirror each other to the alternation of the perceptual and cognitive perspectives.